Pectoralis muscle area and its association with indices of disease severity in interstitial lung disease. (September 2021) - Molgat-Seon, Yannick; Guler, Sabina A.; Peters, Carli M.; Vasilescu, Dragoş M.; Puyat, Joseph H.; Coxson, Harvey O.; Ryerson, Christopher J.; Guenette, Jordan A.
Abstract: Rationale: The pathophysiology of interstitial lung disease (ILD) impacts body composition, whereby ILD severity is linked to lower lean mass. Objectives: To determine i) if pectoralis muscle area (PMA) is a surrogate for whole-body lean mass in ILD, ii) whether PMA is associated with ILD severity, and iii) if the longitudinal change in PMA is associated with pulmonary function and mortality in ILD. Methods: Patients with ILD (n = 164) were analyzed retrospectively. PMA was quantified from a chest computed tomography scan. Peripheral oxygen saturation (SpO2 ), 6-min walk distance (6MWD), and pulmonary function were obtained as part of routine clinical care. Dyspnea and quality of life were assessed using the UCSD Shortness of Breath Questionnaire and European Quality of Life 5 Dimensions questionnaire, respectively. Results: PMA was associated with whole-body lean mass ( p < 0.001). After adjusting for age, sex, height, body mass, and prednisone status, PMA was associated with %-predicted forced vital capacity (FVC), %-predicted diffusion capacity (DLCO ), resting and exertional SpO2, and dyspnea (all p < 0.05), but not forced expiratory volume in 1 s (FEV1 ), FEV1 /FVC, 6MWD, or quality of life (all p > 0.05). The annual negative PMA slope was associated with annual negative slopes in FVC, FEV1, and DLCO (all p < 0.05), but not FEV1 /FVC ( p = 0.46). Annual slope in PMA was associated with all-cause mortality (hazard ratio = −0.80, 95% CI:0.889–0.959; p < 0.001). Conclusion: In patients with ILD, PMA is a suitable surrogate for whole-body lean mass. A lower PMA is associated with indices of ILD severity, which supports the notion that ILD progression may involve sarcopenia. Highlights: Pectoralis muscle area (PMA) is correlated with muscle mass in patients with interstitial lung disease (ILD). A lower PMA is associated with indices of ILD severity. Declines in PMA are associated with ILD-related changes in pulmonary function and mortality. PMA could be used to evaluate ILD prognosis.